1996
DOI: 10.1101/gad.10.24.3202
|View full text |Cite
|
Sign up to set email alerts
|

Fab-7 functions as a chromatin domain boundary to ensure proper segment specification by the Drosophila bithorax complex.

Abstract: Fab-7 deletions in the bithorax complex have a novel gain-of-function phenotype, typically transforming parasegment 11 (PSll) into PS12 identity. Genetic analysis indicates that removal of the Fab-7 element results in the fusion of the lab-6 (PSll) and iab-7 (PS12) cis-regulatory domains into a single regulatory domain that inappropriately regulates Abdominal-B in PSll. This has led to the hypothesis that Fab-7 is a chromatin domain boundary that normally functions to ensure the autonomous activity of the iab-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
217
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(237 citation statements)
references
References 47 publications
17
217
0
1
Order By: Relevance
“…For the enhancer blocker assay in human cell line, the XhoI fragments from LML were cloned into the modified pJC54 vector whereas for the repressor assay the fragments were amplified and cloned into NdeI site upstream to the enhancer. For Drosophila transgenic constructs, XhoI fragments from LML were inserted at XhoI site of the ftzEN:hsp70/lacZ (pCfhL) vector 23 (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the enhancer blocker assay in human cell line, the XhoI fragments from LML were cloned into the modified pJC54 vector whereas for the repressor assay the fragments were amplified and cloned into NdeI site upstream to the enhancer. For Drosophila transgenic constructs, XhoI fragments from LML were inserted at XhoI site of the ftzEN:hsp70/lacZ (pCfhL) vector 23 (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…2a) 23 . GE5 (394 bp), GE7 (389 bp) and GE10 (930 bp) from the human Y chromosome ( Supplementary Fig.…”
Section: Gata Ssr Functions As Enhancer Blocker In Human Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phrase denotes (nonexclusively): alternative looping that brings into action a given CRM under given circumstances and other CRMs under other circumstances; insulators that prevent more proximal CRMs from interacting with a BTA while permitting more distal ones to so interact (e.g., refs. [22][23][24]; insulators that, in certain developmental circumstances, transfer a given CRM to an inaccessible or sequestered chromatin domain (e.g., see refs. 25 and 26); and distant locus activators that, if bound by the factors for which they contain target sites permit more proximal CRMs to be active, probably by means of loop formation with them (27)(28)(29).…”
Section: External Functions (E Operators)mentioning
confidence: 99%
“…Genetic, transgenic, and molecular studies have identified a number of classes of distinct cis-regulatory elements within the iab regions capable of directing abdA and AbdB expression. Insulator DNAs have been identified at the boundaries of the iab8-iab7 domains (Frontabdominal-8, Fab8) (4), iab7-iab6 domains (Fab7) (5)(6)(7)(8)(9)(10), and iab5-iab4 domains (Miscadastral pigmentation, Mcp) ( Fig. 1 A) (7,11).…”
Section: E Xpression Of the Abdominal-a (Abda) And Abdominal-b (Abdb)mentioning
confidence: 99%